Nanotechnology and Matrix Metalloproteinases in Cancer Diagnosis and Treatment - Gonzalez-Avila, Georgina; Sommer, Bettina; García-Hernandez, A. Armando; Ramos, Carlos; Flores-Soto, Edgar (Frontiers in Molecular Biosciences, 2022)
Cancer is still one of the leading causes of death worldwide. This great mortality is due to its late diagnosis when the disease is already at advanced stages. Although the efforts made to develop more effective treatments, around 90% of cancer deaths are due to metastasis that confers a systemic character to the disease and the neoplastic cell resistance to therapies. Likewise, matrix metalloproteinases (MMPs) are endopeptidases that participate in all the events of the metastatic process. MMPs’ augmented concentrations and a large enzymatic activity have been considered as bad prognosis markers of the disease. Knowledge about MMPs expression, molecular structure, and functions will allow the development of therapies that might hinder their participation in cancer progression. In this context, nanotechnology applied to medicine offers the opportunity to formulate therapeutic agents that can act directly on a target cell, avoiding side effects and improving the diagnosis, follow-up, and treatment of a disease. The goal of the present review is to discuss novel nanotechnological strategies in which MMPs are used with theranostic purposes in cancer.